CLASSROOM ACTIVITIES IN COMMUNICATIVE LANGUAGE TEACHING - Arif Ma'mun Rifa'i (Institut Agama Islam Ngawi, 2018)
AbstractsEducation is so important to human life, and it is the inevitable tool in their communication. The demanding using international language is coming urgent, because, currently, the foreigners’, companies’ and business’ mobility is so increasingly move so high without frontier.This paper explain how the classroom activities in adopting communicative language teaching. It is based on the necessity that language learning and teaching is inseparable with language competence, according to this the situation and condition in the classroom need to be design as appropriate as possible focus on communicative language competence.Everyone deal with the essence of language is communicative. Communicative competence implies both understanding and producing appropriate words and other communication forms in ways that will make sense not only to the speaker/actor but also to others. The language classroom ideally adopts the communicative practice that refers to activities where it practices in using language within a real communicative context is the focus, where real information is exchanged. Key words : Classroom Activities, Communicative competence